2019
DOI: 10.1002/cbin.11246
|View full text |Cite
|
Sign up to set email alerts
|

HIF‐1α forms regulatory loop with YAP to coordinate hypoxia‐induced adriamycin resistance in acute myeloid leukemia cells

Abstract: Despite the improvement in acute myeloid leukemia (AML) treatments, most patients had a poor prognosis and suffered from chemoresistance and disease relapse. Therefore, there is an urgent need for elucidation of mechanism(s) underlying drug resistance in AML. In the present study, we found that AML cells showed less susceptibility to adriamycin (ADR) in the presence of hypoxia, while inhibition of hypoxia‐inducible factor 1α (HIF‐1α) by CdCl2 can make AML cells re‐susceptibile to ADR even under hypoxia. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Generally, in the nucleus, YAP mainly relied on multiple domains to interact with transcription factors to form complexes, promoting the expression and activation of downstream target genes [11,20]. Bin Zhu et al reported that YAP sustained HIF-1α stability and promoted HIF-1α's activity on the target gene pyruvate kinase M2 (PKM2), thereby inducing chemoresistance in acute myeloidleukemia under hypoxia [30]. Recent study has demonstrated that HMGB1 triggered both YAP and HIF-1α nuclear translocation and enhanced YAP and HIF-1α interaction promoting pancreatic cancer stemness [19].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in the nucleus, YAP mainly relied on multiple domains to interact with transcription factors to form complexes, promoting the expression and activation of downstream target genes [11,20]. Bin Zhu et al reported that YAP sustained HIF-1α stability and promoted HIF-1α's activity on the target gene pyruvate kinase M2 (PKM2), thereby inducing chemoresistance in acute myeloidleukemia under hypoxia [30]. Recent study has demonstrated that HMGB1 triggered both YAP and HIF-1α nuclear translocation and enhanced YAP and HIF-1α interaction promoting pancreatic cancer stemness [19].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we conclude that cCr interferes with cell growth, inhibits cell cycle progression, and impairs chemotaxis/cell invasion likely through both its effects on cellular metabolism as well as microtubule dynamics. Of note, YAP expression has also been shown to correlate with HIF-dependent adriamycin (DOX) resistance in leukemia [100]. And, down-regulation of CKB in Skov3 ovarian cancer cells enhanced sensitivity to doxorubicin [72].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HIF-1αhigh-expression-mediated microenvironment hypoxia in MSC is one of the important triggers of the niches tumorous process (37). Hypoxia can not only enhance the adhesion and chemotaxis between LSC and MSC, but also reduce the sensitivity of LSC to chemotherapy drugs (39,40).…”
Section: Discussionmentioning
confidence: 99%